2010
DOI: 10.1002/pro.340
|View full text |Cite
|
Sign up to set email alerts
|

Pyrroline‐5‐carboxylate synthase and proline biosynthesis: From osmotolerance to rare metabolic disease

Abstract: Pyrroline-5-carboxylate synthase (P5CS) is a bifunctional enzyme that exhibits glutamate kinase (GK) and c-glutamyl phosphate reductase (GPR) activities. The enzyme is highly relevant in humans because it belongs to a combined route for the interconversion of glutamate, ornithine and proline. The deficiency of P5CS activity in humans is associated with a rare, inherited metabolic disease. It is well established that some bacteria and plants accumulate proline in response to osmotic stress. The alignment of P5C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 74 publications
(123 reference statements)
1
95
0
Order By: Relevance
“…Single amino acid substitutions that abrogate the allosteric regulation by proline can be found at many positions in the ␥-glutamyl kinase protein sequence of both prokaryotes and eukaryotes (for an overview, see the study by Perez-Arellano et al [50]). The crystal structure of the E. coli ␥-glutamyl kinase (49,51) revealed that the glutamate substrate binding site partially overlaps with that of the feedback inhibitor proline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single amino acid substitutions that abrogate the allosteric regulation by proline can be found at many positions in the ␥-glutamyl kinase protein sequence of both prokaryotes and eukaryotes (for an overview, see the study by Perez-Arellano et al [50]). The crystal structure of the E. coli ␥-glutamyl kinase (49,51) revealed that the glutamate substrate binding site partially overlaps with that of the feedback inhibitor proline.…”
Section: Discussionmentioning
confidence: 99%
“…1D). The anabolic proline biosynthesis pathway in microorganisms is frequently regulated biochemically through allosteric feedback inhibition of the activity of the first proline-biosynthetic enzyme (ProB) by the end product proline (16,23,45,(49)(50)(51).…”
mentioning
confidence: 99%
“…P5CS is a bifunctional adenosine triphosphate (ATP) and an NAD(P)H-dependent enzyme in higher eukaryotes that displays glutamate kinase (GK) and c-glutamyl phosphate reductase (GPR) activities (49,110). In primitive organisms such as bacteria and yeast, GK and GPR are monofunctional enzymes (6,94). The structure of bifunctional P5CS has not been reported, but individual structures of GK and GPR are available from bacteria (79,89).…”
Section: Proline Metabolic Enzymesmentioning
confidence: 99%
“…It has been confirmed that D-1-pyrroline-5-carboxylate synthetase is encoded by two differentially regulated genes in different plant species (Turchetto-Zolet et al, 2009). Usually one of the P5CS isoforms is osmo-regulated and the other is associated with developmentally governed processes (Hur et al, 2004;Székely et al, 2008;Pérez-Arellano et al, 2010).…”
Section: D-1-pyrroline-5-carboxylate Synthetase (P5cs)mentioning
confidence: 97%
“…It has been proved to be a very effective singlet oxygen quencher (Alia et al, 2001). The first two steps of proline biosynthesis in plants are catalyzed by the bifunctional enzyme D-1-pyrroline-5-carboxylate synthetase (P5CS, EC not assigned) that encompasses both γ-glutamyl kinase and glutamic-γ-semialdehyde dehydrogenase activities (Pérez-Arellano et al, 2010). P5CS plays a key role in plant intracellular accumulation of proline and is subjected to feedback inhibition by proline, controlling the level of the free imino acid under both normal and stress conditions (Hong et al, 2000).…”
Section: D-1-pyrroline-5-carboxylate Synthetase (P5cs)mentioning
confidence: 99%